Crystal structure of 2-(4-(dimethylamino)-2-fluorophenyl)-1,3-bis(1H-1,2,4-triazol-1-yl)propan-2-ol monohydrate, C15H20FN7O2 - Liu Shao-Hua; Tang Mi; Cheng Li-Hua; Shen Shi-Gang (Zeitschrift für Kristallographie - New Crystal Structures, 2017)
C15H20FN7O2, triclinic, P1̅ (no. 2), a = 5.8088(18) Å, b = 11.667(4) Å, c = 13.104(4) Å, α = 68.724(4)°, β = 84.660(5)°, γ = 84.859(4)°, V = 822.4(4) Å3, Z = 2, Rgt(F) = 0.0501, wRref(F2) = 0.1394, T = 293(2) K.